Investigation of stability and dynamics of photosynthetic pigment - protein complexes using optical spectroscopy - Odermatt, Mirjam (Jihočeská univerzita, 2021)
Isolated violaxanthin-chlorophyll a binding protein of Nannochloropsis oceanica was studied by optical spectroscopy, putting a specific focus on time-resolved fluorescence spectroscopy. Thereby, dynamic and kinetic information about the pigment-protein interactions with respect to non-photochemical quenching was collected utilizing pigment and intrinsic tryptophan fluorescence. Using this method, the investigation of the molecular environment of the pigment-protein complex during the process of qE was possible.
Investigation of stability and dynamics of photosynthetic pigment - protein complexes using optical spectroscopy
Keywords: violaxanthin-chlorophyll a protein; VCP; non-photochemical quenching; NPQ; aggregation of LHC; light-harvesting complexes; intrinsic tryptophan fluorescence; time-resolved fluorescence; optical spectroscopy; pigment-protein complexes; violaxanthin-chlorophyll a protein; VCP; non-photochemical quenching; NPQ; aggregation of LHC; light-harvesting complexes; intrinsic tryptophan fluorescence; time-resolved fluorescence; optical spectroscopy; pigment-protein complexes